Inovasi Pengolahan Limbah Organik UMKM Desa Gunung Muda menjadi Pupuk Organik Cair Bernilai Tinggi - Ardiansyah, Ari; ⁠Nur Apriani; Redika Cindra Reranta; Ikbal; ⁠Anggraini Aprilia Putri; Deasy Antika; Tyas Nabila Agustin; Sepriyanto Andika Putra; Wanda Novia Adana; Ramadhani (Amaliah: Jurnal Pengabdian Kepada Masyarakat, 2024)
This study aims to process organic waste produced by MSMEs in Gunung Muda Village into high-value liquid organic fertilizer using liquid EM4 fertilizer as a fermentation agent. The types of waste used include vegetable, fruit, and other organic waste. The study was conducted for one month in August 2024, with a mixed-method approach that combines quantitative and qualitative methods. The fermentation process showed that liquid EM4 fertilizer effectively accelerated the decomposition of organic waste into liquid organic fertilizer within 14 days. The results of the analysis showed that the liquid organic fertilizer produced had good nutritional content and met the standards for liquid organic fertilizer for agriculture. In addition, respondents consisting of village communities and MSME owners showed high interest in using and supporting the production of this liquid organic fertilizer. This study indicates that this organic waste processing innovation not only offers environmental solutions but also has the potential to improve the economic welfare of village communities. Further support is needed to ensure the sustainability of this program, including community training and collaboration with local governments.